2022
DOI: 10.1051/0004-6361/202142061
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of a magnetic flux rope associated with a major flare in the solar active region 12205

Abstract: Solar eruptions are often generated as a result of the complex magnetic environment in solar active regions (ARs). Unravelling the relevant structure and evolution is vital to disclosing the underlying mechanisms that initiate such eruptions. In this work, we conduct a comprehensive study of the magnetic field structure and evolution responsible for a major flare eruption in a complex AR: NOAA 12205. The study is based on a detailed analysis of observations from the SDO and a time sequence of coronal magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…No signature common to earlier twisted flux emergence simulations (e.g., Fan 2001;Magara & Longcope 2001;Manchester et al 2004;Archontis & Török 2008) can be identified. In addition, we cannot find any large-scale twisting motion (as modeled in Török & Kliem 2003;Aulanier et al 2005b;Jiang et al 2021), nor any systematic and well-aligned series of converging motions and photospheric flux cancellations (e.g., van Ballegooijen & Martens 1989;Forbes & Priest 1995;Aulanier et al 2010;Amari et al 2011;Zuccarello et al 2015;Duan et al 2022). Therefore, despite the pre-reconnecting lines organizing into the aforementioned arcade and flux rope at the onset of reconnection (Figures 7d and 7e), they do not begin as these coherent structures beforehand (Figures 7a-7c).…”
Section: Deviations From Previous Studiesmentioning
confidence: 71%
“…No signature common to earlier twisted flux emergence simulations (e.g., Fan 2001;Magara & Longcope 2001;Manchester et al 2004;Archontis & Török 2008) can be identified. In addition, we cannot find any large-scale twisting motion (as modeled in Török & Kliem 2003;Aulanier et al 2005b;Jiang et al 2021), nor any systematic and well-aligned series of converging motions and photospheric flux cancellations (e.g., van Ballegooijen & Martens 1989;Forbes & Priest 1995;Aulanier et al 2010;Amari et al 2011;Zuccarello et al 2015;Duan et al 2022). Therefore, despite the pre-reconnecting lines organizing into the aforementioned arcade and flux rope at the onset of reconnection (Figures 7d and 7e), they do not begin as these coherent structures beforehand (Figures 7a-7c).…”
Section: Deviations From Previous Studiesmentioning
confidence: 71%
“…the integral follows the path of a magnetic field line from one footpoint to the other. Following [30], we estimate the averaged twist number corresponding to the MFR volume with |T w | 1 and found the maximum values of averaged twist number to be 1.98 and 2 for the MHD and HMMD cases, respectively. Previous studies regarding the threshold value for kink-instability (see [30] and the references therein) suggest that if the averaged twist number ranges between 1.5 to 2.5, the MFR is stable against kink.…”
Section: Simulation Resultsmentioning
confidence: 99%